Method for testing and judging performance of laser local soft region
Through the hardness testing and data analysis of the laser local soft zone samples, the problem of difficulty testing and judging the performance of local soft zone performance of laser local soft regions was solved, and the guidance of effective assessment and parameter adjustment of laser softening technology was realized.
Patent Information
- Application Number
- CN202411450231.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-17
AI Technical Summary
It is difficult for the prior art to effectively test and judge the performance of the local soft zone of the laser, especially when there is no obvious change in the surface of the part after laser softening processing.
The steps of sampling, sample processing, hardness testing, and data analysis include the hardness testing of the laser local soft area sample, and determine whether the performance of the soft zone performance in accordance with the hardness distribution curve meets the specified standards.
A simple and reliable method can effectively test and judge the performance of local soft areas of laser, determine whether the laser softening process is normal, and guide the adjustment of laser softening parameters.
Smart Images

Figure CN119375024A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile component performance testing, in particular to a method for testing and judging the performance of a laser local soft zone. Background Art
[0002] In recent years, new energy vehicle technology and market have developed rapidly. In order to save energy and reduce emissions, automobile lightweighting is particularly critical. Using hot-formed steel to replace traditional low-carbon steel in the body-in-white can reduce weight while improving the collision performance of the body, and its weight reduction effect can reach up to 30%. At present, the proportion of hot-formed steel used in different models is 10-30%. With the rapid development of automobile lightweight technology, the application of hot-formed steel on the body is increasing, and the strength is also increasing. Along with this are some refined technical requirements, such as local softening, which is mainly aimed at the high hardness of hot-formed parts and the difficulty in the subsequent riveting process; or obtaining a local soft zone before spot welding to improve the performance of the heat-affected zone of the weld and avoid cracking of the weld. In the already published Chinese patent (publication number 2022108273302), a variable strength partial performance test method for 2Gpa hot-formed materials is introduced, but it uses mold soft zone technology, which is characterized by a tensile strength of 700-850MPa in the soft zone and a width of 30-50mm in the transition zone.
[0003] However, the shortcomings of the prior art are that, for the laser soft zone, the soft zone tensile strength range, the size of the soft zone and the transition zone and their shape distribution are different from those in the above patents, and the above patent content method cannot be used to judge whether the laser softening technical parameters are qualified. In the laser local softening process, since there is no obvious change on the surface of the part after the laser softening process, the existing patent cannot test and judge the performance of the soft zone. Summary of the invention
[0004] To this end, the technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for testing and evaluating the performance of a local laser soft zone. The method of the present invention is simple and reliable, and can be used to test the laser soft zone performance of hot-formed parts. A set of evaluation criteria for the method is provided to determine whether the performance of the laser soft zone meets the standards and whether the laser softening process is normal, thereby facilitating the guidance of the adjustment of the laser softening parameters.
[0005] In order to solve the above technical problems, the present invention provides a method for testing and judging the performance of a laser local soft zone, comprising:
[0006] Step S1, sampling step, sampling from the hot-formed part to obtain a laser local soft zone specimen to be tested;
[0007] Step S2, sample processing step, cutting the laser local soft zone sample, obtaining a test surface, and processing the test surface until there are no obvious scratches on the test surface; the test surface includes a hard zone, a transition zone, and a soft zone;
[0008] Step S3, a hardness testing step, performs a hardness test on the surface to be tested, wherein the hardness testing method includes method A, method B and method C.
[0009] The method A is to perform a hardness test on the soft area of the surface to be tested along the longitudinal direction to obtain hardness test data of the upper surface and the lower surface of the soft area of the surface to be tested;
[0010] The method B is to perform a hardness test on the surface to be tested in the transverse direction to obtain a plurality of hardness test data of the surface to be tested in the transverse direction, wherein the test range covers the soft area, transition area and hard area of the surface to be tested;
[0011] The method C is to perform a hardness test on the surface to be tested along a first direction to obtain a plurality of hardness test data of the surface to be tested along the first direction, wherein the test range covers a soft area, a transition area and a hard area of the surface to be tested, and the first direction and the transverse direction have an angle;
[0012] Step S4, a data analysis step, draws a hardness distribution curve based on the hardness test data measured in the method A, the method B and the method C to determine whether the soft zone performance of the surface to be tested meets the specified standard.
[0013] In one embodiment of the present invention, in step S4, according to the hardness test data measured by method A, if the lower surface hardness value minus the upper surface hardness value ≤ 30HV, it is judged that the laser local soft zone sample is completely softened and has a consistent hardness;
[0014] If the lower surface hardness value minus the upper surface hardness value>30HV, it is determined that the laser local soft zone sample is not completely softened;
[0015] If the lower surface hardness value minus the upper surface hardness value is less than -15 HV, it is determined that the laser local soft zone sample is partially austenitized.
[0016] In one embodiment of the present invention, in step S4, for the hardness distribution curve, if the hardness distribution curve is symmetrically U-shaped and the width of the transition zone is 6-10 mm, it is judged that the performance of the laser local soft zone sample is normal; if the width of the transition zone is greater than 10 mm, it is judged that the laser speed is too fast or the defocus amount is too large;
[0017] If the hardness distribution curve is U-shaped, but the curve on one side of the U-shape is higher, it is judged that the laser scanning speed is too fast;
[0018] If the hardness distribution curve is W-shaped, it is judged that the temperature in the center area of the soft zone has reached the austenitizing temperature.
[0019] In one embodiment of the present invention, in step S3, method A includes performing hardness tests on multiple longitudinal indentations in a soft zone of the test surface to obtain upper surface hardness data and lower surface hardness data of the soft zone along the longitudinal direction.
[0020] In one embodiment of the present invention, in step S3, method B includes performing hardness tests on multiple transverse indentations near the upper surface, the middle area, and the lower surface of the test surface, wherein the transverse indentations cover the soft area, the transition area, and the hard area, to obtain multiple hardness test data.
[0021] In one embodiment of the present invention, in step S3, method C includes performing indentation tests on a plurality of continuous points along the first direction on the surface to be tested, the point range covers the soft zone, the transition zone and the hard zone, and the angle between the first direction and the lateral direction is 10-90°.
[0022] In one embodiment of the present invention, in step S3, the distance between two adjacent indentations is 0.1-4 mm.
[0023] In one embodiment of the present invention, in step S2, the step of obtaining the surface to be measured includes step S21, cutting the laser local soft area sample in half along the midline of the soft area surface and perpendicular to the surface, and using the thickness section of the laser local soft area sample as the surface to be measured.
[0024] In one embodiment of the present invention, in step S1, the distance between the sampling range and the boundary of the laser local soft zone to be tested is greater than 15 mm; in step S2, the method of cutting the laser local soft zone sample includes wire cutting or water-cooled grinding wheel cutting.
[0025] In one embodiment of the present invention, in step S3, the hardness testing method includes a Rockwell hardness testing method or a Vickers hardness testing method.
[0026] The above technical solution of the present invention has the following advantages compared with the prior art:
[0027] The method for testing and judging the performance of a laser local soft zone described in the present invention comprises a sampling step, a sample processing step, a hardness testing step and a data analysis step. The method of the present invention is simple and has high reliability. The hardness test of the laser local soft zone sample to be tested is realized through the above steps, and the data obtained from the hardness test is analyzed to judge whether the performance of the laser soft zone meets the standard, and then judge whether the laser softening process is normal. It can also serve as a reference and guide in the subsequent adjustment process of the laser softening parameters. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0029] Figure 1 It is a top view schematic diagram of the laser soft zone distribution and sampling range of the preferred embodiment of the present invention.
[0030] Figure 2 It is a schematic diagram of the test position and test direction of the hardness test of the laser soft zone in the preferred embodiment of the present invention.
[0031] Figure 3 Graph showing the hardness distribution of method A according to a preferred embodiment of the present invention.
[0032] Figure 4 1 is a hardness distribution curve diagram of method B and method C according to a preferred embodiment of the present invention.
[0033] Figure 5 It is a schematic diagram of the top view structure of the sampling range in a specific implementation manner of the present invention.
[0034] Figure 6 yes Figure 5 Hardness curve distribution of the soft area of the sample. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0036] Reference Figures 1 to 6 As shown, the present invention discloses a method for testing and judging the performance of a laser local soft zone, comprising step S1, a sampling step, sampling from a hot formed part to obtain a laser local soft zone specimen to be tested.
[0037] The method further comprises step S2, a sample processing step, cutting the laser local soft zone sample, obtaining a test surface, and processing the test surface. Specifically, the test surface is inlaid and polished until there are no obvious scratches on the test surface. The test surface includes a hard zone (parent material zone), a transition zone, and a soft zone;
[0038] Step S3, a hardness testing step, performs a hardness test on the surface to be tested, and the hardness testing method includes method A, method B and method C, wherein:
[0039] The method A is to perform a hardness test on the soft area of the surface to be tested in the longitudinal direction to obtain a plurality of hardness test data of the upper surface and the lower surface of the soft area of the surface to be tested;
[0040] The method B is to perform a hardness test on the surface to be tested in the transverse direction to obtain a plurality of hardness test data of the surface to be tested in the transverse direction, wherein the test range covers the soft area, transition area and hard area of the surface to be tested;
[0041] The method C is to perform a hardness test on the surface to be tested along a first direction to obtain a plurality of hardness test data of the surface to be tested along the first direction, wherein the test range covers a soft area, a transition area and a hard area of the surface to be tested, and the first direction and the transverse direction have an angle;
[0042] Step S4, a data analysis step, judging whether the soft zone performance of the surface to be tested meets the specified standard according to the hardness test data measured by the method A;
[0043] According to the hardness test data obtained in the method B and the method C, a hardness distribution curve is drawn, and it is determined according to the hardness distribution curve whether the soft zone performance of the surface to be tested meets the specified standard.
[0044] It can be known that the method for testing and judging the performance of a laser local soft zone to be protected by the present invention includes a sampling step, a sample processing step, a hardness testing step and a data analysis step. The method of the present invention is simple and has high reliability. The hardness test of the laser local soft zone sample to be tested is realized through the above steps, and the data obtained from the hardness test is analyzed to determine whether the performance of the laser soft zone meets the standard, and then determine whether the laser softening process is normal. It can also serve as a reference and guide in the subsequent adjustment of the laser softening parameters.
[0045] It should be noted that the present invention is applicable to hot-formed parts after laser local softening treatment, and the materials of the hot-formed parts include but are not limited to bare plates, aluminum silicon coated plates, zinc-based coated plates, etc. When selecting a single hot-formed part, the thickness of the selected hot-formed part is 0.6-4mm, the hardness of the hot-formed part is 400-590HV, and the tensile strength is 1300-2000MPa.
[0046] The hardness of the laser local soft zone on the hot formed part is 230-480HV, and the tensile strength is 800-1500MPa.
[0047] As a preferred implementation, in step S4, combined with Figure 3 As shown in curve ①, according to the hardness test data measured by method A, if the lower surface hardness value - the upper surface hardness value ≤ 30HV, it is judged that the laser local soft zone sample is completely softened and the hardness is consistent.
[0048] Combination Figure 3 As shown in curve ②, if the lower surface hardness value - the upper surface hardness value > 30HV, it is judged that the laser local soft zone sample is not completely softened. The main reason for the incomplete softening is that the laser scanning speed is too fast.
[0049] Combination Figure 3 As shown in curve ③, if the lower surface hardness value minus the upper surface hardness value is less than -15HV, it is judged that the laser local soft zone sample is partially austenitized, and the hardness increases again after air cooling. This situation mainly occurs when the upper surface softening temperature exceeds 880°C, and the laser power is high at this time.
[0050] It needs to be explained that austenitization refers to the metal heat treatment process in which steel is heated above the critical point to form austenite. The heated workpiece is heated to a temperature above the eutectoid temperature so that the ferrite and cementite at room temperature are transformed back into austenite.
[0051] Further, in step S4, for the hardness test data obtained in the method B and the method C, in the hardness distribution curve drawn according to the hardness test data:
[0052] Combination Figure 4 As shown in curve ④, if the hardness distribution curve is symmetrically U-shaped and the width of the transition zone is 6-10mm, it is judged that the performance of the laser local soft zone sample is normal. If the width of the transition zone is greater than 10mm, it is judged that the laser speed is too fast or the defocus amount is too large;
[0053] Combination Figure 4 As shown in curve ⑤, if the hardness distribution curve is U-shaped, but the curve on one side of the U-shape is higher, it is judged that the laser scanning speed is too fast;
[0054] Combination Figure 4 As shown in curve ⑥, if the hardness distribution curve is W-shaped, it is judged that the temperature of the central area of the soft zone has reached the austenitizing temperature, and the hardness increases again after air cooling. This situation occurs when the temperature of the soft zone exceeds 880°C, and the laser power is too high. Then, hardness tests are performed on the upper, middle and lower layers of the soft zone respectively. The lower the layer, the more austenitized areas of the soft zone are.
[0055] Combination Figure 2 From the perspective of FIG. 1 , in the step S3 , the method A specifically includes, on the surface to be tested, performing hardness tests on multiple longitudinal indentations in the soft zone of the surface to be tested to obtain upper surface hardness data and lower surface hardness data of the soft zone along the longitudinal direction.
[0056] Combination Figure 2 As shown, in the step S3, the method B includes, on the surface to be tested, performing hardness tests on multiple transverse indentations near the upper surface, the middle area, and near the lower surface, the transverse indentations cover the soft area, the transition area, and the hard area, to obtain multiple hardness test data.
[0057] according to Figure 2 From the perspective of the present invention, in step S3, the method C includes performing an indentation test on a plurality of continuous points along the first direction on the surface to be tested, the point range covers the soft zone, the transition zone and the hard zone, and the angle between the first direction and the lateral direction is 10-90°.
[0058] In detail, the angle is related to the ratio of the cross-sectional area of the soft zone to the thickness of the sample. The larger the ratio, the smaller the angle.
[0059] In step S3, the distance between two adjacent indentations is 0.1-4 mm. In addition, the position and number of indentations can be adjusted according to actual conditions.
[0060] As a preferred embodiment, in the step S2, the step of obtaining the surface to be measured includes step S21, cutting the laser local soft area sample in half along the midline of the soft area surface and perpendicular to the surface, and using the thickness section of the laser local soft area sample as the surface to be measured.
[0061] As a preferred implementation, in the step S1, the distance between the sampling range and the boundary of the laser local soft zone to be tested is greater than 15 mm.
[0062] In the step S2, the method of cutting the laser local soft zone sample includes wire cutting or water-cooled grinding wheel cutting.
[0063] In the step S3, the hardness testing method includes a Rockwell hardness testing method or a Vickers hardness testing method.
[0064] A specific implementation of the present invention is described in detail below with reference to the accompanying drawings:
[0065] To facilitate the explanation of this method, the following is a case study using a laser softening area of 20*20mm as an example:
[0066] (1) First, take a sample from a 1500MPa grade hot-formed part with a thickness of 1.6mm and remove the laser local soft zone sample to be tested. The sample size is as follows: Figure 5 As shown,
[0067] (2) The laser local soft zone sample is cut in half along the vertical thickness direction, and then the sample thickness section is used as the test surface, and inlaying, grinding and polishing are performed until there are no obvious scratches on the test surface.
[0068] (3) Perform Vickers hardness test on the tested surface, select test method B, perform hardness test every 2 mm in the middle layer in the thickness direction of the soft zone, draw a hardness distribution diagram, analyze the hardness data, and Figure 6 As shown, the results show that the hardness of the soft zone is 260-270HV, the width of the soft zone is 14mm, the transition zone is 6-8mm, and the hardness distribution curve is symmetrical U-shaped. The results show that the performance of the soft zone is stable and the laser parameters are in line with expectations.
[0069] In the description of the embodiments of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "setting" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0070] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0071] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0072] Obviously, the above embodiments are merely examples for the purpose of clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for testing and judging the performance of a laser local soft zone, characterized in that: include, Step S1, sampling step, sampling from the hot-formed part to obtain a laser local soft zone sample to be tested; Step S2, sample processing step, cutting the laser local soft zone sample, obtaining a test surface, and processing the test surface until there are no obvious scratches on the test surface; the test surface includes a hard zone, a transition zone, and a soft zone; Step S3, a hardness testing step, performs a hardness test on the surface to be tested, wherein the hardness testing method includes method A, method B and method C. The method A is to perform a hardness test on the soft area of the surface to be tested along the longitudinal direction to obtain hardness test data of the upper surface and the lower surface of the soft area of the surface to be tested; The method B is to perform a hardness test on the surface to be tested in the transverse direction to obtain a plurality of hardness test data of the surface to be tested in the transverse direction, wherein the test range covers the soft area, transition area and hard area of the surface to be tested; The method C is to perform a hardness test on the surface to be tested along a first direction to obtain a plurality of hardness test data of the surface to be tested along the first direction, wherein the test range covers a soft area, a transition area and a hard area of the surface to be tested, and the first direction and the transverse direction have an angle; Step S4, a data analysis step, draws a hardness distribution curve based on the hardness test data measured in the method A, the method B and the method C to determine whether the soft zone performance of the surface to be tested meets the specified standard.
2. A method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In the step S4, according to the hardness test data measured by the method A, if the lower surface hardness value minus the upper surface hardness value ≤ 30HV, it is judged that the laser local soft zone sample is completely softened and has a consistent hardness; If the lower surface hardness value minus the upper surface hardness value>30HV, it is determined that the laser local soft zone sample is not completely softened; If the lower surface hardness value minus the upper surface hardness value is less than -15 HV, it is determined that the laser local soft zone sample is partially austenitized.
3. A method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In the step S4, for the hardness distribution curve, if the hardness distribution curve is symmetrically U-shaped and the width of the transition zone is 6-10 mm, it is judged that the performance of the laser local soft zone sample is normal; if the width of the transition zone is greater than 10 mm, it is judged that the laser speed is too fast or the defocus amount is too large; If the hardness distribution curve is U-shaped, but the curve on one side of the U-shape is higher, it is judged that the laser scanning speed is too fast; If the hardness distribution curve is W-shaped, it is judged that the temperature in the center area of the soft zone has reached the austenitizing temperature.
4. A method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In step S3, the method A includes, on the surface to be tested, performing hardness tests on a plurality of longitudinal indentations in a soft zone of the surface to be tested to obtain upper surface hardness data and lower surface hardness data of the soft zone along the longitudinal direction.
5. A method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In step S3, method B includes performing hardness tests on multiple transverse indentations near the upper surface, the middle area, and the lower surface of the test surface, wherein the transverse indentations cover the soft area, the transition area, and the hard area, to obtain multiple hardness test data.
6. A method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In step S3, method C includes performing indentation tests on a plurality of consecutive points along the first direction on the surface to be tested, the point range covers the soft zone, the transition zone and the hard zone, and the angle between the first direction and the lateral direction is 10-90°.
7. A method for testing and judging the performance of a laser local soft zone according to claim 5, characterized in that: In the step S3, the distance between two adjacent indentations is 0.1-4 mm.
8. A method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In step S2, the step of obtaining the surface to be measured includes cutting the laser local soft area sample in half along the midline of the soft area surface and perpendicular to the surface, and using the thickness section of the laser local soft area sample as the surface to be measured.
9. A method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In the step S1, the distance between the sampling range and the boundary of the laser local soft zone to be tested is greater than 15 mm; in the step S2, the method of cutting the laser local soft zone sample includes wire cutting or water-cooled grinding wheel cutting.
10. The method for testing and judging the performance of a laser local soft zone according to claim 1, characterized in that: In the step S3, the hardness testing method includes a Rockwell hardness testing method or a Vickers hardness testing method.
Citation Information
Patent Citations
Multi-point indentation device and system for soft material and testing method
CN116337664A
Local softening process for hot stamping part
CN116590499A
Shape measurement device and shape measurement method
JP2013221799A
Method for evaluating bending property of molded object
JP2024139029A
Method of measuring geometric parameters of steel sheet moving by roller table and laser measuring system for its implementation
RU2621490C1
Cited By
Experimental method for testing microhardness of plated layer of plated steel plate
CN116698638A